Regulation of Small Intestinal Epithelial Homeostasis by Tsc2-mTORC1 Signaling - SETIAWAN, JAJAR (Kobe J Med Sci, 2019)
Mammalian target of rapamycin complex 1 (mTORC1), a protein complex containing the serine/threonine kinase mTOR, integrates various growth stimulating signals. mTORC1 is expressed in intestinal epithelial cells (IECs), whereas the physiological roles of this protein complex in homeostasis of IECs remain virtually unknown. We here generated mice, in which tuberous sclerosis complex 2 (Tsc2), a negative regulator of mTORC1, was specifically ablated in IECs (Tsc2 CKO mice). Ablation of Tsc2 enhanced the phosphorylation of mTORC1 downstream molecules such as ribosomal S6 protein and 4E-BP1 in IECs. Tsc2 CKO mice manifested the enhanced proliferative activity of IECs in intestinal crypts as well as the promoted migration of these cells along the crypt-villus axis. The mutant mice also manifested the increased apoptotic rate of IECs as well as the increased ectopic Paneth cells, which are one of the major differentiated IECs. In addition, in vitro study showed that ablation of Tsc2 promoted the development of intestinal organoids without epidermal growth factor, while mTORC1 inhibitor, rapamycin, diminished this phenotype. Our results thus suggest that Tsc2-mTORC1 signaling regulates the proliferation, migration, and positioning of IECs, and thereby contributes to the proper regulation of intestinal homeostasis.